O discurso sobre o posicionamento intercultural do sujeito na política nacional do livro didático para educação do campo - Melo, Maria Aparecida Vieira de (2020)
ABSTRACT Education, as a social practice, positions social subjects in different ways as can be verified throughout Brazilian and Latin American history. Recently, it was observed the appearance of a discursive order that excels in the difference and cultural diversity in education. This event is felt in the territory of field education through social movements where the subjects of the field assume affirmative positions and functions of valuing their rights, their culture, their knowledge and commitments to social transformation, thus breaking with the hegemonic discourse about education within the culture of the dominant elites. In this context, interculturality, as a táticfor strengthening the social movements of the field,is part of a counter hegemonic and decolonial perspective. Considering this assumption, this research has as the siss the assertion that interculturality functions as a guiding principle of the position of the subject of the field in the National TextbookPolicy. Thus, its general objective aims to analyze the intercultural positioning of the peasant subject in the order of the discourse of field education and, as specific objectives, to map the source texts that underlie the PNLD/field; identify the series of signs that evidence the different positions of the subject of the field; describe the beams of relationships that specify the position of the subject of the field; to elucidate discursive orders related to the intercultural position of the subject ofthe field and, finally, to explain the functioning of interculturality as a guiding principle of the making of the PNLD/field. The theoretical/methodological toolbox adopted is the archaeological analysis of Michel Foucault's discourse (2008), which offers us the conditions to answer the following questions: what beams of relationships are triggered in the PNLD/fieldto define the positions of the subjects of the field? What series of signs constitute the discursive order of the PNLD/field? What are the correreports of interculturality demarcated the position of the subject of the field? The initial sources of this research are: PNLD/field-2013 and 2016. Some PNLD/fieldfindings point to the intercultural position of the subject of the field, linked to democracy, human rights, the decolonial perspective and cultural studies. For, the position of the subjects of the field crosses the subjects in their singularities and particularities, emphasizing their differences in the midstof the intercultural diversity of which they are positioned in the national policy of the textbook for field education.